A Nonlinear Finite Element Modeling For High Strength Fibrous Reinforced Concrete Beams - Muhammad, Jaza Hassan; Abdulqader, Mohamed Rauof (Sulaimani Journal for Engineering Sciences, 2017)
This paper presents a nonlinear finite element model to investigate the influence of steel fibers on the flexural strength of high strength reinforced concrete beams. Two methods had been used to model the steel fiber using ANSYS 14. In the first model the effect of steel fiber on the mechanical properties of concrete has been neglected, and the steel fiber considered as smeared reinforcement. In the second model the effect of steel fiber on the mechanical properties of concrete is considered in material modeling. The theoretical results were compared with the experimental result. And the variable present in both models was fiber volume fraction (0.00, 0.75, and 1.5) %. The experimental beams consist of high strength steel fiber reinforced concrete rectangular beams with sectional dimension ( 150 x 100 ) mm and overall length (3000) mm simply supported, and loaded through two points loading, those beams are used for verification of the proposed models. Results showed that the first model is more reliable and compatible with experimental results than the second model. The analytical models also showed that increase in volume fraction of steel fiber improves the flexural rigidity and flexural strength of the high-strength fiber reinforced concrete beams.
Keywords: high strength concrete; reinforced concrete beams; ANSYS 14; steel fiber; deflection